GO-DACT : a phase 3b randomised, double-blind, placebo-controlled trial of GOlimumab plus methotrexate (MTX) versus placebo plus MTX in improving DACTylitis in MTX-naive patients with psoriatic arthritis - Vieira De Sousa, Elsa Cristina (2020)
© author(s) (or their employer(s)) 2020. Re-use permitted under CC BY- nC. no commercial re-use. see rights and permissions. Published by BMJ. This is an open access article distributed in accordance with the Creative Commons Attribution Non Commercial (CC BY-NC 4.0) license.